Sliding benchmarks might prevent de-selection of talented badminton players - Johan Pion; Mohd Rozilee Wazir Norjali Wazir; Irene Faber; Kathryn Johnston; Pieter Vansteenkiste; Matthieu Lenoir; Tengku Fadilah Kamalden (Universidad de Granada, 2025)
Despite potential advantages of talent identification practices, the degree of bias in decision-making due to relative age and maturity timing remains a concern. To investigate the impact of relative age and maturity on selection processes, and to examine the possible influence of an intervention aimed at minimizing the impact of relative age and maturity biases, thirty-three boys (Mage = 12.43y ± 0.36y) invited to compete for Badminton Malaysia, completed three anthropometrical measures, eight physical performance assessments, and five motor coordination tests. These players were tracked throughout their career to determine pathway progression (i.e., dropout or continuation) and their level of success (i.e., season-end rankings). With regards to the relative age of athletes and the initial selection to the U13 team, findings revealed that younger and less mature players were disadvantaged, since their morphology, physical fitness, and motor capacities were less developed than their peers. A sliding benchmark intervention was applied, where raw scores were adjusted. Although, the dropout rate from the U13 team was high (24/33 players, 73%), 6 of 9 remaining players of the national team achieved exceptional results, which were evident six years later. As a result of the sliding benchmark intervention, two relatively younger, late maturers with superior motor competence scores, were selected to the elite sport school. Without this intervention, both players might never have won the U21 World Championships. This paper examines the pathway of these competitive badminton athletes and discusses the potential value of applying a sliding benchmark intervention in competitive sport selection settings.